2012
DOI: 10.1177/2048872612463542
|View full text |Cite
|
Sign up to set email alerts
|

Self-referral to chest pain units: results of the German CPU-registry

Abstract: Background: Chest pain units (CPUs) are increasingly established in emergency cardiology services. With improved visibility of CPUs in the population, patients may refer themselves directly to these units, obviating emergency medical services (EMS). Little is known about characteristics and outcomes of self-referred patients, as compared with those referred by EMS. Therefore, we described self-referral patients enrolled in the CPU-registry of the German Cardiac Society and compared them with those referred by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
2
8
0
2
Order By: Relevance
“…Interestingly, and in contrast to self-referral, referral by an EMS turned out to be another independent variable for early TTE. As shown in a previous analysis by our group, a possible explanation may be that self-referrals are made by patients who are younger, less severely ill and are more likely to have noncoronary problems (ACS in about 30%) than those calling the EMS [28]. On the other hand, it might also be a hint that medical awareness within the CPU is higher if an EMS track has been started prior to arrival.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, and in contrast to self-referral, referral by an EMS turned out to be another independent variable for early TTE. As shown in a previous analysis by our group, a possible explanation may be that self-referrals are made by patients who are younger, less severely ill and are more likely to have noncoronary problems (ACS in about 30%) than those calling the EMS [28]. On the other hand, it might also be a hint that medical awareness within the CPU is higher if an EMS track has been started prior to arrival.…”
Section: Discussionmentioning
confidence: 97%
“…The analyses of the high portion of self-referrals currently started a discussion of providing an improved low-threshold access in the CPUs for patients' self-referral to allow better early detection of severe cardiac disorders. 22 However, beside the first positive impression of the standard-of-care in German CPUs, recent data also revealed that not all patients receive medical therapy following current guidelines and even if the outcome data are promising, the rate of rehospitalization remains high. At the moment, further studies are yet on their way focusing on guideline-adherence in German CPUs.…”
Section: The German Cpu-registrymentioning
confidence: 98%
“…Patienten, die sich fußläufig in der CPU vorstellten, waren in der Regel jünger, weniger schwer erkrankt und hatten eher nicht koronare Probleme als diejenigen, die einen Notfalldienst anriefen. Dennoch hatte eine hohe Anzahl (30 %) der Patienten, die sich selbst überwiesen, ein ACS [16]. Die Brustschmerzambulanz wird z.…”
Section: Kur Zgefasstunclassified